Pengaruh Kompetensi Pegawai dan Komitmen Terhadap Efektivitas Kerja Pegawai: (Studi Persepsional pada Pegawai Dinas Koperasi, Perindustrian Dan Perdagangan Kabupaten Ciamis) - Tetty Herlyanty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is motivated by the low effectiveness of employee work. This is thought to be due to the lack of productivity in the implementation of main tasks and functions due to the lack of knowledge, insight and technology which of course relates to employee competence. The low effectiveness of employee work is also thought to be due to the slow implementation of work programs from the planning that has been set on the grounds that there are many jobs that are difficult to do. The purpose of this study is to determine how employee competence affects employee work effectiveness, how commitment affects employee work effectiveness, and how employee competence and commitment together affect employee work effectiveness. The method used in this study uses a quantitative descriptive method. To analyze it, statistical correlation and multiple regression test data analysis was used using SPSS version 22.00. The results of the study obtained provide the conclusion that employee competence has a positive and significant effect on employee work effectiveness, commitment has a positive and significant effect on employee work effectiveness, and employee competence and commitment have a positive and significant effect on employee work effectiveness.